Sustainable Development: Needs, Values, Rights. (1st February 1993) - Redclift, Michael
Abstract : 'Sustainable development' is analysed as a product of the Modernist tradition, in which social criticism and understanding are legitimized against a background of evolutionary theory, scientific specialization, and rapid economic growth. Within this tradition, sustainable development emphasizes the need to live within ecological limits, but allows the retention of an essentially optimistic idea of progress. However, the inherent contradictions in the concept of sustainable development may lead to rejection of the Modernist view in favour of a new vision of the world in which the authority of science and technology is questioned and more emphasis is placed on cultural diversity.